Hubungan antara Pengobatan Komplementer dengan Kualitas Hidup pada Pasien Diabetes Mellitus - Nur Yusrin Husnati; Anita Kustanti; Heny Suseani Pangastuti (Jurnal Keperawatan Klinis dan Komunitas (Clinical and Community Nursing Journal), 2017)
Background: Diabetes mellitus is a chronic disease that can affect physical, psychological, social and spiritual functional activity that requires special approach and treatment to improve patient's quality of life. One of treatments to improve quality of life is therapy management with alternative and complementary medicine.Objective: To determine the correlation between the use of complementary medicine with the quality of life among diabetes mellitus patients.Methods: This study used an analytic survey with cross-sectional design. Respondents involved in this study were 120 respondent diabetes mellitus patients in Yogyakarta city from August to September 2017 with purposive sampling technique. This study used Diabetes Quality of Life Clinical Trial Questionnaire-Revised Parameter (DQLCTQ-R) questionnaire to measure quality of life among diabetes mellitus patients. Researchers also included questions about the use of complementary therapies to measure the use of complementary therapies. Contingency coefficient correlation test was used to analyze the data statistically.Results: Most patients did not use complementary medicine (53,3%). Most users of complementary and non-complementary medicine had the same high quality of life (60,71% and 56,25%). The correlation test values between complementary medicine and quality of life in patients with diabetes mellitus showed p value = 0,621 (p> 0,05) and r = 0,045.Conclusion: There was no significant correlation between the uses of complementary medicine with quality of life among diabetes mellitus patients.ABSTRAKLatar  belakang: Diabetes mellitus  merupakan  penyakit  kronis  yang  dapat  mempengaruhi  aktivitas fungsional  fisik,  psikologis,  sosial  dan  spiritual  yang  memerlukan  pendekatan  dan  pengobatan  khusus untuk  meningkatkan  kualitas  hidup  pasien.  Salah  satu  perawatan  untuk  meningkatkan  kualitas  hidup adalah manajemen terapi dengan pengobatan komplementer.Tujuan: Mengetahui hubungan antarapengobatan komplementer dengan kualitas hidup pasien diabetes mellitus.Metode:  Penelitian  ini  menggunakan  survei  analitik  dengan  desain cross-sectional.  Responden  yang dilibatkan dalam penelitian ini 120 pasien diabetes mellitus di Kota Yogyakarta dari bulan Agustus sampai September 2017 yang diambil dengan teknik purposive sampling. Penelitian ini menggunakan kuesioner Diabetes  Quality  of  Life  Clinical  Trial  Questionnare-Revised  Parameter (DQLCTQ-R) untuk  megukur kualitas  hidup  pasien  diabetes  mellitus. Peneliti  juga  mencantumkan  pertanyaan  tentang  penggunaan terapi komplementeruntuk mengukur penggunaan terapi komplementer. Uji korelasi koefisien kontingensi digunakan untuk menganalisis secara statistik.Hasil:  Mayoritas  pasien  tidak menggunakan  pengobatan  komplementer  (53,3%).  Mayoritas  pengguna pengobatan komplementer dan bukan pengguna pengobatan komplementer sama-sama memiliki kualitas hidup yang tinggi (60,71% dan 56,25%). Nilai uji korelasi antara pengobatan komplementer dengan kualitas hidup pada pasien diabetes mellitus menunjukkan nilai p = 0,621 (p> 0,05) dan r = 0,045.Kesimpulan:Tidak  ada  hubungan  yang  signifikan  antarapengobatan  komplementer  dengan  kualitas hidup pada pasien diabetes mellitus.